The reliability and validity of a newly developed self-rating functional scale compared with Personal and Social Performance Scale and World Health Organization Disability Assessment Schedule II. (January 2019) - Zhao, Yan-Jie; He, Yan-Ling; Zhang, Li-Li; Qiao, Ying; Zhao, Jing-Ping; Si, Tian-Mei; Wang, Gang; Zhang, Ning; Ning, Yu-Ping; Zhang, Ming-Yuan
Abstract : A new self-rating functional scale (SRFS) was developed to assess the functionality of patients with schizophrenia, referred to the structure of Personal and Social Performance Scale (PSP). The main aim of this study was to evaluate the reliability and validity of the SRFS. A total of 210 patients with schizophrenia were recruited from outpatient clinics in six sites in China. Demographic information, SRFS, PSP, World Health Organization Disability Assessment Schedule II, and Positive and Negative Syndrome Scale were assessed. Spearman's correlation coefficient and path analysis were used to assess the reliability and validity of the SRFS. Cronbach's α coefficient was used to assess the internal consistency reliability. Cronbach's α was 0.83, and ranged from 0.80 to 0.82 stably, indicating that the scale was reliable in internal consistency. Spearman's correlation coefficient between split two parts was 0.68 ( P <0.01), suggesting a moderate to strong split-half reliability. The standardized regression coefficients ranged from 0.48 to 0.79, indicating moderate construct validity. Spearman's correlation coefficients between SRFS and PSP, World Health Organization Disability Assessment Schedule II, and Positive and Negative Syndrome Scale are 0.59, 0.65, and 0.47 (all P <0.01), respectively, indicating moderate criteria validities. The SRFS is a reliable and valid instrument for assessing personal and social functionality in patients with schizophrenia. Abstract : Supplemental Digital Content is available in the text.